Učni korpus SSJ in leksikon besednih oblik za slovenščino - Arhar Holdt, Špela (Jezik in slovstvo, 2009)
The main purpose of the article is the presentation of the preparation of the training corpus and the lexicon of word forms for Slovene. With a scope of 400,000 words, the existing corpus presupposes four-level manually checked annotation: lemmatisation, morphosyntactic and syntactic annotation, and named entity recognition. Together with the JOS100k corpus, the SSJ corpus forms a training corpus of half a million entries for training statistical models, such as for the purposes of morphosyntactic tagging and parsing of Slovene texts. The lexicon will provide approximately 100,000 units, containing morphological paradigms of individual words with a selection of data, in line with the JOS system of morphosyntactic annotation. The inclusion of information about the (derivational) connectedness of lexical units is foreseen, and in the case of observed form variation in language use we will also include information about the frequency of forms and the current definition in normative sources. The inclusion of multiword units is foreseen on the level of multiword proper nouns and forms for which there are variants that are written together and apart.
Keywords: korpusna lingvisitka; lastna imena; leksikonske enote; Slovene; slovenščina; učni korpus